Perancangan Sistem Perpustakaan Berbasis Web Pada SD Negeri 85 Kota Bengkulu - A.R Walad Mahfuzhi; Agung Kharisma Hidayah; Anisya Sonita; Devano Checario (UNIVED Press, 2025)
The development of information technology drives digital transformation in various fields, including elementary school library management. SD Negeri 85 Bengkulu City still uses a manual system for recording book borrowing and returning, resulting in frequent problems such as recording errors, data loss, and service delays. This study aims to design a web-based library system that can simplify the process of book data management, collection searches, and recording borrowing and returning more effectively, efficiently, and structured. The development method used is the Waterfall model, with a focus on the needs analysis and system design stages. The analysis process is carried out through observation, interviews, and literature studies to identify user needs. The results of the study are a system design consisting of a UML (Use Case and Activity Diagram) diagram, an Entity Relationship Diagram (ERD) for database design, and a simple and user-friendly user interface mockup. This system design is expected to be a reference in the development of a web-based library system at SD Negeri 85 Bengkulu City so that it can improve management efficiency, minimize recording errors, and provide easy access to book information for students and teachers.